Organized crime in Kosovo and the international community (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
Ten years after the 2008 declaration of independence, the same leaders who guided the KLA during the 1998-1999 conflict now hold the highest offices in the Republic of Kosovo. International institutions repeatedly investigated their involvement in war crimes, illegal trades and elimination of political opponents, but never obtained final convictions. Through the analysis of criminal proceedings involving four political leaders, the article will show that the same NATO countries that intervened in support to the KLA, and then led the international missions tasked with administering justice in Kosovo, often supported the current political elite, including in some cases by interfering with the outcome of judicial proceedings, in a bid to promote the country’s political stability.Keywords: Kosovo, war crimes, Balkans, international organized crime, Kosovo Liberation Army (KLA)